The Influence of Financial Knowledge, Income, and Lifestyle on Financial Behavior of Housewives at Laut Dendang Village - Qahfi Romula Siregar; Jumeida Simatupang (Journal of International Conference Proceedings (JICP), 2022)
After Covid 19, many changes have occurred regarding the process of understanding and managing finances in the community. Changes in life certainly affect the family's understanding of financial management, income and lifestyle on financial behavior. The population in this family study is in Laut Dendang Village, Deli Serdang Regency. Research by taking a sample of 100 housewives as a sample. This study uses Judgment Sampling, where the sample is selected from a population based on expert considerations and scientific considerations. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study uses a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study conclude that partially there is a significant effect of the variable financial knowledge on financial behavior, there is significant effect of the variable income on financial behavior, and there is significant effect of the variable lifestyle on financial behavior. And there is simultaneously significant effect of the variable financial knowledge, income and lifestyle effect on financial behavior. Keywords: Financial Knowledge, Income, Lifestyle and Financial Behavior.